2005
DOI: 10.1002/jnr.20432
|View full text |Cite
|
Sign up to set email alerts
|

The secreted brain-derived neurotrophic factor precursor pro-BDNF binds to TrkB and p75NTR but not to TrkA or TrkC

Abstract: The neurotrophin brain-derived neurotrophic factor (BDNF) binds to two cell surface receptors: TrkB receptors that promote neuronal survival and differentiation and p75NTR that induces apoptosis or survival. BDNF, as well as the other members of the neurotrophin family, is synthesized as a larger precursor, pro-BDNF, which undergoes posttranslational modifications and proteolytic processing by furin or related proteases. Both mature neurotrophins and uncleaved proneurotrophins are secreted from cells. The bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 39 publications
7
56
0
1
Order By: Relevance
“…For this purpose, pro-BDNF protein produced using conditioned media from COS-7 cells transfected with furinresistant pro-BDNF (Fayard et al, 2005) was quantified with the BDNF Emax Immunosystem and used as standard. After coating a 96-well plate with mouse anti-BDNF (provided in BDNF Emax Immunosystem), nerve lysates and 25, 50, 100, 200, and 250 pg/ml pro-BDNF standard were added.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, pro-BDNF protein produced using conditioned media from COS-7 cells transfected with furinresistant pro-BDNF (Fayard et al, 2005) was quantified with the BDNF Emax Immunosystem and used as standard. After coating a 96-well plate with mouse anti-BDNF (provided in BDNF Emax Immunosystem), nerve lysates and 25, 50, 100, 200, and 250 pg/ml pro-BDNF standard were added.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike p75NTR and TrkA, sortilin shows considerably higher affinity for proNGF than for NGF (5 nM versus 90 nM, respectively), and proNGF promotes formation of heterotrimeric complexes containing sortilin and p75NTR (15). However, some studies have indicated that proneurotrophins are not selective p75NTR ligands and that they are capable of binding and activating Trk receptors to exert a neurotrophic, rather than a pro-apoptotic effect (16,17).…”
mentioning
confidence: 99%
“…Unlike p75NTR and TrkA, sortilin shows considerably higher affinity for proNGF than for NGF (5 nM versus 90 nM, respectively), and proNGF promotes formation of heterotrimeric complexes containing sortilin and p75NTR (15). However, some studies have indicated that proneurotrophins are not selective p75NTR ligands and that they are capable of binding and activating Trk receptors to exert a neurotrophic, rather than a pro-apoptotic effect (16,17).In this study, we have compared proneurotrophin binding to p75NTR and TrkA and determined the signaling events acti-* This work was supported, in whole or in part, by National Institutes of Health Grant NS24380.This work was also supported by Grant MOP37850 from the Canadian Institute of Health Research (CIHR) and a grant from the United States Public Health Service. The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 99%
“…A previous study failed to observe pericellular processing of furin-resistant pro-BDNF [19], however, Arg 125 within the furin consensus motif had been mutated to Ala, inadvertently destroying the plasmin-cleavage site identified here. From the observed activity of plasmin-processed BDNF against TrkB and the known apoptotic effects of pro-BDNF [9], this pericellular processing would be expected to shift a pro-apoptotic response towards a pro-survival effect.…”
Section: Discussionmentioning
confidence: 47%